Palliative sedation at the end of life: prevalence, characteristics and possible determinants - Maria Isabel Carrasco-Zafra; Ricardo Ocaña-Riola; Rafael Gómez-García; Maria Luisa Martín-Roselló; Encarnación Blanco-Reina (BMC Palliative Care)
Abstract Background Palliative Sedation (PS) at the end of life is practiced and perceived differently by health professionals depending on the geographical location in which they provide their health care. Taking into account this heterogeneity, it is necessary to expand knowledge and provide data on this clinical practice in different contexts and countries. On the other hand, the identification of factors associated with PS could help healthcare professionals, at an early stage, to identify patients more likely to require sedation. The aim of this study was to describe the prevalence and characteristics related to PS in a specialised Palliative Care setting, as well as to analyse factors that could be associated with this procedure. Methods This was a cross-sectional study including n = 533 patients who died during the study period in a Palliative Care Unit. Clinical and functional (Barthel and Palliative Performance Scale) variables and the level of complexity were collected. For each patient we assessed whether PS had been performed and, if so, we described the type of sedation, continuity and depth, refractory symptoms, medication used, informed consent and place of death. A multivariate logistic regression model was used to analyse the relationship between several independent variables and PS. Results The prevalence of PS was 16.7% (n = 82). Most frequent refractory symptoms were delirium (36.1%), pain (31.9%) and dyspnoea (25%). Factors associated with having a higher odds of PS were having already started treatment with strong opioids (OR = 2.10; 95% CI = 1.16–3.90) and a lower dependency for activities of daily living (OR = 0.41; 95% CI = 0.23–0.70) on admission at PC. Informed consent for sedation was given mainly by representation and only in 19% of cases by the patient himself. Conclusions Early opioid use and functional status act as factors associated with PS, becoming as clinical evaluations of particular interest during the disease trajectory, which could help to improve individualised care plans for patients at the end of life.